2004
DOI: 10.1212/wnl.62.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive TMS of the motor cortex improves ipsilateral sequential simple finger movements

Abstract: The authors' results support the concept of an interhemispheric "rivalry." They demonstrate the utility of repetitive transcranial magnetic stimulation to explore the functional facilitation of the unstimulated counterpart motor cortex, presumably via suppression of activity in the stimulated motor cortex and transcallosal inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
3
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(176 citation statements)
references
References 64 publications
8
153
3
12
Order By: Relevance
“…The time window (i.e., 60 -75 ms) of these effects is in line with previous studies revealing visual suppression by occipital TMS (Amassian et al, 1989), and is traditionally believed to correspond to the peak of the first volley of feedforward input in visual cortex (Martinez et al, 1999). Although transient disruption of brain function predominates in TMS research, there are also reports of functional improvements (Seyal et al, 1995;Walsh et al, 1998;Hilgetag et al, 2001;Paus, 2002, 2003;Kobayashi et al, 2004;Thut et al, 2005), similar to the RT facilitation we observed. Several studies further showed that stimulation of a given area can induce opposing (disruptive or facilitative) effects depending on task or behavioral context (Walsh et al, 1998;Paus, 2002, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The time window (i.e., 60 -75 ms) of these effects is in line with previous studies revealing visual suppression by occipital TMS (Amassian et al, 1989), and is traditionally believed to correspond to the peak of the first volley of feedforward input in visual cortex (Martinez et al, 1999). Although transient disruption of brain function predominates in TMS research, there are also reports of functional improvements (Seyal et al, 1995;Walsh et al, 1998;Hilgetag et al, 2001;Paus, 2002, 2003;Kobayashi et al, 2004;Thut et al, 2005), similar to the RT facilitation we observed. Several studies further showed that stimulation of a given area can induce opposing (disruptive or facilitative) effects depending on task or behavioral context (Walsh et al, 1998;Paus, 2002, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, other authors found similar paradoxical improvements in performances of hand movements or memory encoding after low-frequency rTMS over motor cortex or ventrolateral prefrontal cortex (Kobayashi et al, 2004;Kahn et al, 2005). A similar mechanism has been observed in animal models, in which a new lesion in the superior colliculus was shown to improve the visual dysfunction initially caused by an ipsilateral occipito-parietal lesion (Kapur, 1996;Lomber et al, 2002).…”
Section: Functional Role Of the Right Pitcsupporting
confidence: 59%
“…TMS of the motor cortex that increased its excitability improved performance in a procedural learning task (Pascual-Leone et al 1999). TMS in suitable areas has also been found beneficial in a motor task (Butefisch et al 2004), motor learning (Nitsche et al 2003), visuo-motor coordination tasks (Antal et al 2004a, b), working memory (Fregni et al 2005), finger sequence tapping (Kobayashi et al 2004), classification (Kincses et al 2004) and even declarative memory consolidation during sleep (Marshall et al 2004). Alan Snyder and colleagues claim to have demonstrated how TMS inhibiting anterior brain areas could change the drawing style of normal subjects into a more concrete style and improve spell-checking abilities, presumably by reducing top-down semantic control (Snyder et al 2003;Snyder 2004).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%